Apparatus for time-dependent measurements of mechanical properties under hydrostatic pressure - Kralj, Aleš (Kovine zlitine tehnologije, 1999)
Although high hydrostatic pressure commonly appear in demanding structural applictions and during several manufacturing processes, there is little information available about their effect on material properties. This is because, world-wide, very few instruments exist that can measure the effects of hydrostatic pressure on mechanical properties. Fillers, Moonan and Tschoegl built such an instrument several years ago. We have improved and upgraded this apparatus with the intention of researching the influence of pressure and temperature on the mechanical properties of time dependent polymeric materials. In this study, special emphasis is put on the Filles-Moonan-Tschoegl (FMT) model, which can describe the combined effect of temperature and pressure. The model is based on the time, temperature and pressure superposition principle, for which parameters are obtained using the presented apparatus. As an example we present measurements on PVAc for bulk creep compliance and shear relaxation.
Keywords: polimeri; tlak; aparature; mehanske lastnosti; merjenje